2016
DOI: 10.1186/s13046-016-0417-9
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of mutant p53 by capsaicin, the major constituent of peppers

Abstract: BackgroundMutations in the p53 oncosuppressor gene are highly frequent in human cancers. These alterations are mainly point mutations in the DNA binding domain of p53 and disable p53 from transactivating target genes devoted to anticancer activity. Mutant p53 proteins are usually more stable than wild-type p53 and may not only impair wild-type p53 activity but also acquire pro-oncogenic functions. Therefore, targeting mutant p53 to clear the hyperstable proteins or change p53 conformation to reactivate wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…To explore natural compounds that induce degradation of mutant p53, Garufi et al recently discovered that capsaicin, the constituent of peppers responsible for their pungency, could induce the protein degradation of mutant p53 (R175H, R273H) in both glioblastoma and breast cancer cell lines (67). Abrogation of mutant p53 by capsaicin treatment restored wild-type p53 activities, such as upregulation of PUMA and Bax, and induction of cancer cell death.…”
Section: Compounds That Directly Target Mutant P53mentioning
confidence: 99%
See 1 more Smart Citation
“…To explore natural compounds that induce degradation of mutant p53, Garufi et al recently discovered that capsaicin, the constituent of peppers responsible for their pungency, could induce the protein degradation of mutant p53 (R175H, R273H) in both glioblastoma and breast cancer cell lines (67). Abrogation of mutant p53 by capsaicin treatment restored wild-type p53 activities, such as upregulation of PUMA and Bax, and induction of cancer cell death.…”
Section: Compounds That Directly Target Mutant P53mentioning
confidence: 99%
“…Abrogation of mutant p53 by capsaicin treatment restored wild-type p53 activities, such as upregulation of PUMA and Bax, and induction of cancer cell death. Interestingly, capsaicin also decreased the expression of MDR1 (multidrug resistance gene) and therefore sensitized tumors to chemotherapy drugs such as cisplatin (67). However, the mechanism by which capsaicin induces degradation of mutant p53 remains unknown.…”
Section: Compounds That Directly Target Mutant P53mentioning
confidence: 99%
“…Scientific reports on capsaicin potential carcinogenicity have yielded inconsistent findings (Bode and Dong 2011). Some studies have shown that capsaicin exerts anti-proliferative and pro-apoptotic effects on different cancer cell lines (Brown et al 2010;Díaz-Laviada 2010;Garufi et al 2016;Lau et al 2014) and might inhibit the metabolism of chemical carcinogens by interacting with a number of cytochrome P450 enzymes (CYPs) (Zhang et al 2012). On the other hand, Lee and Park have reported an association between capsaicin at high doses with mutagenicity and carcinogenicity (Lee and Park 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A TP53 (Tumor protein p53) gene mutation has been found in more than half of human cancers, suggesting that the TP53 gene plays a crucial role in suppressing tumor formation [16]. Capsaicin can reactivate mutant p53 in glioblastoma and lung cancer [17]; however, leukemic cells with mutant p53 are insensitive to capsaicin [18]. To resolve this incongruity, I have employed hyperthermia and nonivamide, which is a heat-stable analogue of capsaicin (http://www.hmdb.ca/metabolites/HMDB29846), to examine the anti-tumor effects of capsaicin analogues in U937 cells, which are a leukemic cell type with mutant p53 (46 base pair deletions, beginning at codon 132) [14].…”
Section: Introductionmentioning
confidence: 99%